Basic approaches to a location theory of one public firm. Mit zusammenfassung: Grundlegende Ansätze zur Standortheorie eines öffentlichen Unternehmens - Feng, Xiao; Friedrich, Peter (Estonian Discussions on Economic Policy, 2013)
Public firms are public economic units that take location decisions or are involved in such decisions. There is a lack of location theories that consider this feature. The literature on public facility location theory mainly concerns location of real capital serving economic units. Attempts to formulate a public firm decision-making oriented location theory are offered. Typical location factors of public firms relate to the goals of public firms, their environment and the number of decision-makers involved in the location decisions. A theory of the public firm is presented, that enables to develop a theory of location for public firms. It is introduced to industrial location theory and to location criteria based on investment rules. Its application in relation to public firms achieving welfare or public objectives is also covered. Interventions by the owner lead to more than one decision-maker and to principal agent models. Public firms compete horizontally due to competition among the public owners or public firms competing against each other. The authors mention some results on location choices within the framework of our basic approach.